Type I Interferon Signature in Primary Antiphospholipid Syndrome: Clinical and Laboratory Associations - Palli, Eleni; Kravvariti, Evrydiki; Tektonidou, Maria G. (Frontiers in Immunology, 2019)
Background. Increased expression of type I interferon (IFN)-regulated genes has been described in blood and tissue cells from patients with systemic lupus erythematosus (SLE) and other rheumatic disorders. Only isolated studies have examined the type I IFN gene expression in antiphosholipid syndrome (APS), while efforts to evaluate associations with APS-related factors are scarce. Objective. Our aim was to investigate the type I IFN signature in patients with primary APS (PAPS), SLE/APS, and SLE in comparison with healthy controls, and to evaluate associations with disease-related characteristics. Methods. We measured the type I IFN score, derived from relative expressions of three IFN-inducible genes (MX-1, IFIT-1, and IFI-44) in peripheral blood mononuclear cells from 55 patients with PAPS, 34 with SLE/APS, 48 with SLE, and 28 controls. In patients with PAPS, we performed multivariate regression to examine associations of type I IFN score with their clinical, laboratory and treatment characteristics. Results. Type I IFN score was increased in all patient groups versus controls (p=0.028, p=0.027, p=0.028 for PAPS, SLE/APS, and SLE, respectively). IFI-44 had the most pronounced expression. In patients with PAPS, multivariate linear regression revealed positive associations of type I IFN score with female gender (b-coefficient=0.49; 95% CI 0.04, 0.94; p=0.034) and IgG or IgM anti-β2GPI antibodies (b-coefficient=0.53; 95% CI 0.10, 0.96; p=0.017), and negative associations with age (b-coefficient=-0.02/year; 95% CI -0.04, -0.01; p=0.027) and hydroxychloroquine use (b-coefficient=-0.51; 95% CI-0.96, -0.06; p=0.027). Conclusion. Type I IFN score is increased in PAPS and correlated positively with anti-β2GPI antibodies and negatively with hydroxychloroquine use.